2007
DOI: 10.1109/tasc.2007.898061
|View full text |Cite
|
Sign up to set email alerts
|

SQUID-Based Biosensor for Probing Ion Transporters in Cell Suspensions and Tissue

Abstract: We have developed a SQUID-based technique to probe membrane-bound proteins, such as cation transporters. The method involves excitation of a biological sample with a sinusoidal electric field (0-5 V/cm, 10-300 Hz), detection, with a SQUID magnetometer, of the magnetic field produced by ac currents in the tissue or cell suspension, and calculation of the Fast Fourier Transform (FFT) of the measured response to obtain a spectrum. We find that the harmonic response of budding yeast cells (S. cerevisiae, 10 8 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…The third harmonic is maximal near 1.16 V/cm. Similar field-dependent third harmonic behavior was observed in yeast suspensions [1], [8], [9]. The first harmonic response of the earthworm increased linearly with amplitude (not shown).…”
Section: Harmonic Response Of the Earthwormsupporting
confidence: 71%
See 2 more Smart Citations
“…The third harmonic is maximal near 1.16 V/cm. Similar field-dependent third harmonic behavior was observed in yeast suspensions [1], [8], [9]. The first harmonic response of the earthworm increased linearly with amplitude (not shown).…”
Section: Harmonic Response Of the Earthwormsupporting
confidence: 71%
“…We have previously demonstrated that remote harmonic detection using SQUIDs reduces polarization impedance and field distortion at pickup electrodes [8], [9]. Electrode polarization can be modeled as equivalent complex impedance formed by an electrical double layer containing polar molecules at the interface between the electrodes and biological material resulting in spurious signals especially at low frequencies [13].…”
Section: Harmonic Response Of the Earthwormmentioning
confidence: 99%
See 1 more Smart Citation